Physics Teachers' Acceptance of Multimedia Applications—Adaptation of the Technology Acceptance Model to Investigate the Influence of TPACK on Physics Teachers' Acceptance Behavior of Multimedia Applications - Mayer, Peter; Girwidz, Raimund (Frontiers in Education, 2019)
Although multimedia applications can undeniably have a positive impact on the learning success of students, they are not used by all physics teachers. The study presented in this paper examines the influence of technological knowledge of physics teachers on their acceptance behaviour by adding TPACK of a physics teacher, as an additional variable to an adapted technology acceptance model (TAM). In addition, the TAM has been adapted to study the acceptance of multimedia applications of physics teachers in physics education. For this purpose, both, the design features were adapted and items were reworded to adjust them to the usage of multimedia applications in school and teaching context. While the first part of the study evaluates the changes of the TAM, the second part of the study deals with the extension of the TAM by the factor TPACK. TPACK acts as a superordinate moderator variable, which has a highly significant influence on the adapted TAM’s design features “perceived ease of use“, “perceived usefulness for pupils“ and the “personal job relevance assessment“. Interestingly, the results of the study show that TPACK has no significant influence on the "perceived personal usefulness" of multimedia applications in physics teaching. Nevertheless, the prediction of the acceptance behaviour of multimedia applications in physics teaching can be improved by extending the adapted TAM2/UTAUT model by TPACK.